Unraveling The Mystery. - Vishvaa, KS Sai; Raja., Raja.; Sarathy , Saran Keshav (Journal of Neonatal Surgery, 2025)
Background: Neuroendocrine breast carcinomas (NEBCs) are a unique and, as yet, poorly understood subtype of breast cancer affecting two to five percent of all breast cancers. Because NEBC is histologically similar to invasive ductal carcinoma, it is difficult to diagnose, and immunohistochemistry analysis is also required. Because it is rare, there is no consensus on the best management approaches, and treatment is frequently selected from standard breast cancer regimens. Case Presentation: A case is described of a 77-year-old woman presenting with a right breast tumor that was growing. On clinical examination, the mass in the upper outer quadrant was a 3 × 3 cm oval mass, a firm and movable mass, with no evidence of axillary lymphadenopathy. The two questionable lesions were seen on ultrasound and PET-CT imaging tests. The second lesion was neuroendocrine differentiated invasive carcinoma of no special type, and the first lesion's histopathological analysis was invasive mammary carcinoma with localized neuroendocrine differentiation (30%). Immunohistochemistry was positive for chromogranin expression localized and for synaptophysin positivity high. The tumor was hormone receptor positive; therefore, the patient was started on medication afterwards following a modified radical mastectomy (MRM). Discussion: A localized neuroendocrine differentiation in a primary breast carcinoma demands a careful histopathological and immunohistochemical analysis. There is an early-stage disease due to the lack of distant metastases and locoregional lymphadenopathy. Long-term monitoring is essential, however, because NEBC is unexpected and said to be still the primary course of therapy; however, molecular profiling may help identify new therapeutic targets in the future. Conclusion: It demonstrates the complexity of diagnosis and treatment of NEBC, and put a challenge to improve the reporting of the cases, form the treatment guideline, as well as molecular research of this rare disease. Since such a rare cancer may be treated in such a novel way, there is hope other developments in precision medicine and tailored medicines may improve outcomes for the patient.